Supply-Side Practices and Constraints of the Kola Nut (Cola nitida (Vent) Schott. and Endl.) Value Chain in Ghana: A Descriptive Evidence - Frederick Amon-Armah; Solomon Sefa Oduro; Eric Kofi Doe; Moses Asani; Daniel Nyadanu; Sampson Konlan (International Journal of Agronomy)
The use of kola nut, including natural or alternative medicinal sources, has inevitably created an increased global market demand in excess of its production and provides great prospects for the growth of the kola nut industry in producing countries like Ghana. Nonetheless, there is a great dearth of information on Ghana’s kola nut supply-side practices and constraints that can provide a basis for the development of the industry. This study fills the research gap by describing the practices and constraints of farmers, processors, and marketers of kola nut in Ghana. Using a survey methodology, results showed that nearly all (99.5%) farmers interviewed had not received any extension training on agronomic practices. Low market price of nuts (61.5%) and pests and diseases (60.4%) were the most reported constraints to kola nut production. Chiefs among motivating factors for cultivating kola nut were alternative livelihood support (58%). Some processors (28.6%) who rinsed nuts after depulping used a solution of Akate Master (bifenthrin) and others (51.0%) used fumigation tablets (aluminium phosphide) (91.0%) for storing the nuts. However, these chemicals may be dangerous to the health of consumers in the long run. The low selling price of kola nuts was perceived to be the most (74.8%) constraint to kola nut processing and marketing. Respondents noted that the red nuts were preferred for their durability during transportation and longer shelf life, while the white nuts were preferred for their taste. The results suggest the need for further agronomic, postharvest handling, preservation, and storage, as well as breeding research to provide recommendations to farmers and processors. To overcome some marketing challenges, there is a need for policy support to standardize pricing and grading systems for the mutual benefit of all the stakeholders.